ANALISIS PRODUKSI DAN PENDAPATAN USAHATANI UBI KAYU DI KECAMATAN SEPUTIH BANYAK KABUPATEN LAMPUNG TENGAH - Rika Silvia Anggraini; Dwi Haryono; Fembriarti Erry Prasmatiwi (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2022)
The purposes of this study are to analyze factors that influence cassava production, the cost structure of cassava farming, and the amount of cassava farming income in the Seputih Banyak District, Central Lampung Regency.  The determination of the location of the research was carried out intentionally in the District of Seputih Banyak in Central Lampung Regency.  Respondents in this study were 70 cassava farmers.  This research was conducted in October 2019. This research method uses a survey method.  Data were analyzed using the Cobb-Douglas production function, farm income by calculating Revenue Cost Ratio (R/C), and cost structure.  The results showed that the factors that significantly affected cassava production and gave positive values were seeds and labor, and the factor that gave negative value was urea fertilizer.  The cost structure incurred for variable costs is higher than fixed costs, with the largest total cost structure being the labor cost of 38.56%.  The biggest cost structure for cash costs and calculated costs is 56% of non-family labor costs and 92% of land rent.  Cassava farming is profitable with income from the total cost of IDR11,799,517 per hectare, and R/C value over total cost of 1.67.